(untitled) (Web of Teachers: Inderscience Research, 2025)
The rapid advancement of technology has brought about profound changes in various aspects of human life, including physical activity patterns. This article explores the impact of technology on physical activity levels and behaviors. It examines how modern technologies such as smartphones, social media, video games, and sedentary entertainment options influence individuals’ engagement in physical activity. The article discusses both positive and negative effects, highlighting the potential of technology to promote active lifestyles through innovative solutions such as fitness apps, wearable devices, and virtual fitness classes.